Length of Stay pada Pasien Infark Miokard Akut Tipe Stemi setelah Menjalani Percutaneous Coronary Intervention : a Narrative Review - Firman Sugiharto; Azalia Melati Putri; Aan Nuraeni; Henny Yulianita (Malahayati Nursing Journal, 2023)
ABSTRACT Cardiovascular disease especially ST segment elevation (STEMI) is still a major health problem with high morbidity and mortality rates. Although recent advances in the treatment of STEMI patients have yielded better results, the need for intensive care of patients with a prolonged length of stay (LOS) can increase the burden of health care costs. An understanding of the description of LOS in STEMI patients and the factors that influence it as an effort to improve the quality of care and shorten LOS. To describe length of stay (LOS) in acute myocardial infarction patients with STEMI after treatment percutaneous coronary intervention.This study used narrative review design. The databases used were Pubmed, Ebscohost, Scopus, Taylor and Francis, and Google Scholar. The strategy for searching articles using the PCC framework with the keywords namely “Adults”, “Length of Stay”, “Percutaneous Coronary Intervention” and “Myocardial Infarction”. The results showed that 20 articles were analyzed and most of the articles said that the shortest LOS in STEMI patients after PCI was only 5.9 hours, while the longest LOS was 14 days. Most of the articles said that the LOS in STEMI patients after PCI was prolonged. Many factors affect the duration of LOS in STEMI patients, namely age, gender, complications (bleeding), history of comorbidities (diabetes mellitus, hypertension, and kidney failure), and disease severity are the predictors most experienced by STEMI patients. Keywords: Length of Stay, Myocardial Infarct, STEMI  ABSTRAK Penyakit kardiovaskular khususnya STEMI masih menjadi permasalahan kesehatan utama dengan tingkat morbiditas dan mortalitas yang tinggi. Meskipun kemajuan terbaru dalam penanganan STEMI telah memberikan hasil yang lebih baik, kebutuhan perawatan intensif pasien dengan durasi length of stay (LOS) yang memanjang dapat meningkatan beban biaya perawatan kesehatan. Pemahaman mengenai gambaran LOS pasien STEMI serta faktor yang mempengaruhinya penting diketahui sebagai upaya untuk meningkatkan kualitas perawatan dan mempersingkat LOS. Untuk mendeskripsikan LOS atau lama rawat Pasien Infark miokard dengan STEMI setelah percutaneous coronary intervention. Penelitian ini menggunakan desain narrative review. Basis data yang digunakan meliputi Pubmed, EBSCO-host, Scopus, Taylor and Francis, dan Google Scholar. Strategi pencarian artikel menggunakan kerangka kerja PCC dengan kata kunci “Adults”, “Length of Stay”, “Percutaneous Coronary Intervention” and “Myocardial Infarction”.  Hasil penelitian menunjukkan, dari 20 artikel yang dianalisis, sebagian besar artikel menyebutkan bahwa LOS terpendek pada pasien STEMI pasca PCI hanya 5,9 jam, sedangkan LOS terlama adalah 14 hari. Sebagian besar artikel mengatakan LOS pada pasien STEMI setelah PCI memanjang. Banyak faktor yang mempengaruhi lama LOS pada pasien STEMI yaitu usia, jenis kelamin, komplikasi (perdarahan), riwayat penyakit penyerta (diabetes melitus, hipertensi, dan gagal ginjal), dan tingkat keparahan penyakit merupakan prediktor yang paling banyak dialami oleh pasien STEMI. Kata Kunci: Lama Rawat, Infark Miokardial, STEMI